DETOXIFICATION POTENTIAL OF OCHRATOXIN BY YEAST SLUDGE AND EVALUATION IN BROILER CHICKS - H. Mujahid; A. S. Hashmi; A. A. Anjum; A. Waris; Y. Tipu (Journal of Animal and Plant Sciences, 2012)
Aspergillus ochraceus was cultured using Sabraudיs Dextrose Agar (SDA) and confirmed on the basis of macroscopic and microscopic characters. Ochratoxin was produced on fermented wheat grains, was extracted from the samples by immunoaffinity column. Estimation of ochratoxin was performed by high-performance thin layer Chromatography (HPTLC) against known mycotoxin standard. Broiler chicks (n═150) were purchased and were reared on commercial Broiler feed for 7 days. At the end of first week birds (n═120) were selected on uniform weight basis. Four diets formulated were A (plain feed), B (Ochratoxin A 500ppb), C (Ochratoxin A 500ppb and 1% Yeast sludge) and D (Ochratoxin A 500ppb and 2% Yeast sludge). Completely randomized design (CRD) was adopted for the trial with a total of 12 experimental units. The chicks were fed their respective experimental diets ad libitum for 35 days during which the daily feed consumption, group weight changes and Feed conversion ratio (FCR) were measured.  Feed conversion ratio (FCR) was improved in group D (1.97) followed by A (2.05), B (2.07) and C (2.04). The level of serum total protein and albumin was found to be highest in Group D followed by A, C and B activity of alanine transaminase (ALT) was highest in group B followed by C, D and A. Level of ochratoxin in liver samples collected from group A, B, C and D was 0, 87.5, 57.5 and 43.7 ppb, respectively. Level of ochratoxin in liver samples collected from group A, B, C and D was 0, 116, 89 and 35.5 ppb, respectively. Concludingly detoxification potential in (2) percent yeast sludge was better than (1) percent. Yeast sludge can efficiently used for detoxification of mycotoxins.
Keywords: Aspergillus ochraceus; Ochratoxin; Yeast sludge; FCR; TLC